Rzymskie bóstwo akwatyczne "Tiberinus" w epickiej nar racji "Annales" Enniusza - Stankiewicz, Lucyna (Collectanea Philologica, 2014)
An example of this formula usage is the prayer utterance of one of the national epic’s charac- ter, the Annals of Quintus Ennius (Ann. I 26 Skutsch). Since, for the purposes of literary research, significant is only the first triad of this historic poem, the research was limited to Book I of the work. The realism of portrayed events is a dominant feature of the world depicted in the analyzed work and, in an essential manner, it influenced Roman religious ideals. The prayer of Aeneas to Tiber- inus – the god of the Tiber River, is therefore reviewed in a context of mythological topics taken from Homeric tradition. This sacral utterance is spoken in accordance to certain stylistic and ritual patterns that were in use in Roman poetry.